No effect of intradialytic neuromuscular electrical stimulation on inflammation and quality of life: a randomized and parallel design clinical trial - Ana C. B. Marini (Nature Portfolio, 2021)
Abstract Neuromuscular electrical stimulation (NMES) elicits muscle contraction and has been shown to improvement of quality of life. However, if NMES improvement the quality of life and attenuate the inflammation is not fully understood. Therefore, our aim sought to assess the effects of short-term of intradialytic NMES on inflammation and quality of life in patients with chronic kidney disease patients undergoing hemodialysis. A randomized clinical trial conducted with parallel design enrolled adult hemodialysis patients three times a week during 1 month. Patients were randomly assigned to two groups (control group, n = 11; 4F/7 M) or (NMES group, n = 10; 4F/6 M). Pre-and post-intervention, was measured the high-sensitivity C reactive protein, interleukin-6, interleukin-10, and TNFα by the ELISA, and quality of life was applied using the SF-36. During each hemodialysis session, NMES was applied bilaterally at thigh and calves for 40 min. There was not change in cytokines (hs-CRP, IL-6, IL-10, and TNFα) concentrations time × group interaction. In addition, no difference was found in eight domains of quality of life. In addition, the groups did not differ for muscle strength and muscle mass. In conclusion, we found that intradialytic NMES did not change inflammation neither quality of life.